HUBUNGAN TINGKAT STRES KERJA TERHADAP KINERJA PENATA ANESTESI KOTA PADANG - Fatimah, Fatimah; M. Zuhdi Zulhadi; Leo Agustigno (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Job stress is a serious problem that can affect the performance of health workers, including anesthesiologists. High pressure in carrying out tasks, great responsibility, and dynamic and risky work situations make this profession vulnerable to stress. Common symptoms of stress include irritability, anxiety, and impatience. If not handled properly, job stress can increase the risk of incidents in the operating room, either before, during, or after the anesthesia procedure. Objective: To determine the relationship between job stress levels and the performance of anesthesiologists in Padang City. Method: This study used a descriptive observational research design with a Cross Sectional Study approach, the sampling method was Total Sampling. The samples studied were 41 samples. The Independent Variable is the level of job stress and the dependent variable is performance. Data collection used a questionnaire sheet and Kendall's tau statistical test with a significance level of 0.01. Results: p value = 0.001 was obtained with the Kendall' tau correlation test which had a significance level of 1% (0.001 <0.01), then Ho was rejected, which means that there is a very significant relationship between the level of job stress and nurse performance. The Kendall's Tau correlation coefficient value is -0.521, so there is a negative linear value. Which means that the lower the level of work stress, the higher the performance and vice versa, the higher the work stress, the lower the performance. Conclusion: There is a relationship between the level of work stress and the performance of anesthesiologists in Padang City.